2021
DOI: 10.1042/bcj20200314
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulated microRNA-199a-3p enhances osteogenic differentiation of bone marrow mesenchymal stem cells by targeting Kdm3a in ovariectomized rats

Abstract: Osteoporosis is a prevalent systemic skeletal disorder entailing bone fragility and increased fracture risk, often emerging in post-menopausal life. Emerging evidence implicates the dysregulation of microRNAs (miRNAs or miRs) in the progression of osteoporosis. This study investigated the effect of miR-199a-3p on osteoporosis and its underlying mechanism. We first examplished an ovariectomized (OVX)-induced rat osteoporosis model, and then isolated mesenchymal stem cells (MSCs) from bone marrow of the model ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…High levels of miR-199a-3p were also reported in exosomes from human bone marrow MSCs [ 14 ], and the authors suggested that the transport of miR-199a-3p in MSC exosomes is a component of intercellular communication in the bone niche. When the decrease in bone mass and the increase in body weight shown by ZDF rats ( Figure 1 ) is taken into consideration, this downregulation of miR-199a-3p in ZDF rats is in contrast with reports showing that the enhanced expression of miR-199a-3p promoted adipogenesis from bone-marrow-derived MSCs [ 15 ], while its downregulation enhanced the osteogenic differentiation of bone marrow MSCs in ovariectomized rats [ 16 ]. However, supporting our data, miR-199a-3p was upregulated in osteocytic areas in ovariectomized (OVX) mice and was also an inductor of catabolic bone cell autophagy in osteocyte-like MLO-Y4 cells [ 17 ].…”
Section: Discussionmentioning
confidence: 70%
“…High levels of miR-199a-3p were also reported in exosomes from human bone marrow MSCs [ 14 ], and the authors suggested that the transport of miR-199a-3p in MSC exosomes is a component of intercellular communication in the bone niche. When the decrease in bone mass and the increase in body weight shown by ZDF rats ( Figure 1 ) is taken into consideration, this downregulation of miR-199a-3p in ZDF rats is in contrast with reports showing that the enhanced expression of miR-199a-3p promoted adipogenesis from bone-marrow-derived MSCs [ 15 ], while its downregulation enhanced the osteogenic differentiation of bone marrow MSCs in ovariectomized rats [ 16 ]. However, supporting our data, miR-199a-3p was upregulated in osteocytic areas in ovariectomized (OVX) mice and was also an inductor of catabolic bone cell autophagy in osteocyte-like MLO-Y4 cells [ 17 ].…”
Section: Discussionmentioning
confidence: 70%
“…54 Wu et al have demonstrated that miR-199a-3p can reduce the expression of alkaline phosphatase, Runx2, Osx, and other osteogenic differentiation factors by inhibiting Erk2 phosphorylation, leading to the acceleration of bone loss and the occurrence of OP. 55 Wang et al have demonstrated that miR-29b expression in PBMC of SLE patients is upregulated; AKT kinase is abnormally activated; anti-dsDNA titer is upregulated, and C3 level is downregulated. 56 This is contrary to the expression shown in studies of OP: the expression of miR-29b is significantly downregulated in the bone marrow of OP patients, reducing the activation of AKT kinase, and thereby inhibiting stem cell osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were anesthetized by an intraperitoneal injection of 2% 2,2,2-tribromoethanol (Macklin, Shanghai, China). Then, bilateral ovaries were removed from the OVX rats, while peripheral ovarian fat was removed from the Sham rats, as described previously ( Wu et al, 2021 ). After completion of operation the resuscitated rats were kept in the same conditions as before operation.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometric characterization was performed as described previously ( Wu et al, 2021 ). Briefly, the passage 3 BMSCs were digested with 0.25% trypsin and suspended to a concentration of 1 × 10 6 cells/mL with cell staining buffer (BioLegend, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%